The Recent Advances on Liver Cancer Stem Cells: Biomarkers, Separation, and Therapy. (27th July 2017) - Xiao, Yanhong; Lin, Mei; Jiang, Xingmao; Ye, Jun; Guo, Ting; Shi, Yujuan; Bian, Xuefeng
Abstract : As the third major reason of mortality related to cancer in the world, liver cancer is also the fifth most frequent cancer. Unluckily, a majority of patients succumb and relapse though many progresses have been made in detection and therapy of liver cancer. It has been put forward that in liver cancer, cancer stem cells (CSCs) hold main responsibility for the formation, invasion, metastasis, and recurrence of tumor. Strategies that are intended to target liver CSCs are playing a more and more significant role in supervising the development of liver cancer treatment and assessing new therapeutic methods. Herein, a brief review about molecule markers, signal pathways, separation, and treatment on liver cancer stem cells (LCSCs) is provided in this paper.